Advances in Conceptual Modeling : ER 2012 Workshops CMS, ECDM-NoCoDA, MoDIC, MORE-BI, RIGiM, SeCoGIS, WISM, Florence, Italy, October 15-18, 2012 : Proceedings - Castano, Silvana (edición) ((Lecture Notes in Computer Science ; Information Systems and Application, incl. Internet/Web))
Compilación de las ponencias presentadas en los siete talleres realizados en el marco de la Conferencia Internacional en Modelado Conceptual 2012: 1. CMS, Third International Workshop on Conceptual Modelling of Services; 2. ECDM-NoCoDa, International Workshop on Evolution and Change in Data Management (ECDM) and Non-Conventional Data Access (NoCoDA); 3. MoDIC, International Workshop on Modeling for Data-Intensive Computing; 4. MORE-BI, Second International Workshop on Modeling and Reasoning for Business Intelligence; 5. RIGiM, 4th International Workshop on Requirements, Intentions and Goals in Conceptual Modeling; 6. SeCoGIS, 6th International Workshop on Semantic and Conceptual Issues in Geographic Information Systems; 7. WISM, 9th International Workshop on Web Information Systems Modeling.